Wittgenstein’s Concept of Language Games - Shiva Zaheri Birgani; Mahnaz Soqandi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2020)
Austrian British philosopher Ludwig Wittgenstein is one of the greatest philosophers in the 20th century. He mostly works in analytic philosophical thought in topics as diverse as logic and language, perception and intention, ethic and religion, aesthetic and culture. Philosophers often create their own vocabularies by giving special meanings to ordinary terms and phrases. Wittgenstein coinages the term of “language games” and the ‘private language argument”. His argument on the language is the rules of the use of ordinary language is neither right nor wrong, neither true nor false, the language is merely useful for the particular applications in which they are applied . Language is defined not as a system of representation but as a system of devices for engaging in various sorts of social activity, hence ‘the meaning of the word is its use in the language.